A Perspective on Synthetic Biology in Drug Discovery and Development—Current Impact and Future Opportunities. (June 2021) - David, Florian; Davis, Andrew M.; Gossing, Michael; Hayes, Martin A.; Romero, Elvira; Scott, Louis H.; Wigglesworth, Mark J.
The global impact of synthetic biology has been accelerating, because of the plummeting cost of DNA synthesis, advances in genetic engineering, growing understanding of genome organization, and explosion in data science. However, much of the discipline's application in the pharmaceutical industry remains enigmatic. In this review, we highlight recent examples of the impact of synthetic biology on target validation, assay development, hit finding, lead optimization, and chemical synthesis, through to the development of cellular therapeutics. We also highlight the availability of tools and technologies driving the discipline. Synthetic biology is certainly impacting all stages of drug discovery and development, and the recognition of the discipline's contribution can further enhance the opportunities for the drug discovery and development value chain.